Anisotropic compressibility of the coordination polymer emim[Mn(btc)]. Issue 3 (1st June 2016) - Madsen, Solveig R.; Moggach, Stephen A.; Overgaard, Jacob; Brummerstedt Iversen, Bo
Abstract : The structural response of a negatively charged metal–organic framework to pressure has been studied with single‐crystal X‐ray diffraction in a diamond anvil cell Abstract : The effect of pressure on the crystal structure of a coordination polymer, emim[Mn II (btc)] (emim = 1‐ethyl, 3‐methyl imidazolium cation, btc = 1, 3, 5‐benzene‐tricarboxylate), was investigated with single‐crystal X‐ray diffraction. At 4.3 GPa the unit‐cell volume had decreased by 14% compared with ambient conditions. The unit‐cell contraction is highly anisotropic, with the a ‐ and b ‐axes decreasing by 5.5 and 9.5%, respectively, and the c ‐axis compressing a mere 0.25% up to 1.7 GPa followed by a 0.2% expansion between 1.7 and 4.3 GPa. The 0.2% increase in length of the c ‐axis in this interval happens above the quasi‐hydrostatic limit of the pressure‐transmitting medium and therefore it might be a consequence of strain gradients. Under ambient conditions, two MnO6 units are connected by two carboxylate ligands to form dimeric units. On increasing pressure, a non‐bonded O atom from a bridging carboxylate group approaches the Mn atom, with the Mn—O distance decreasing from 2.866 (1) Å at 0.3 GPa to 2.482 (6) Å at 4.3 GPa, increasing the coordination environment of the Mn ion from six‐ to seven‐coordinated.